4t+2/4t-5=2t+6/2t-7

Simple and best practice solution for 4t+2/4t-5=2t+6/2t-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4t+2/4t-5=2t+6/2t-7 equation:



4t+2/4t-5=2t+6/2t-7
We move all terms to the left:
4t+2/4t-5-(2t+6/2t-7)=0
Domain of the equation: 4t!=0
t!=0/4
t!=0
t∈R
Domain of the equation: 2t-7)!=0
t∈R
We get rid of parentheses
4t+2/4t-2t-6/2t+7-5=0
We calculate fractions
4t-2t+4t/8t^2+(-24t)/8t^2+7-5=0
We add all the numbers together, and all the variables
2t+4t/8t^2+(-24t)/8t^2+2=0
We multiply all the terms by the denominator
2t*8t^2+4t+(-24t)+2*8t^2=0
We add all the numbers together, and all the variables
4t+2t*8t^2+(-24t)+2*8t^2=0
Wy multiply elements
16t^3+16t^2+4t+(-24t)=0
We get rid of parentheses
16t^3+16t^2+4t-24t=0
We do not support etpression: t^3

See similar equations:

| 2x;x=12 | | x+12.8+12.6+11.8+9.7÷5=12.3 | | 3/8x-1/8x+5=10 | | 10.00-d=5420 | | 6x=-6(6-4x) | | Y=150x-60x | | -(-7-2x)+7=-7 | | 3/8c-1/8c+5=10 | | 2x+12=8+18 | | 6/11x+1/3=7/10-5/11x+7/10 | | 4÷l=2 | | x+6.50+0.06(x+6.50)=16.43 | | |x3|=9 | | 5(1.4r)+30r=436.60 | | s+27=44 | | 4÷d=63 | | x=1.903 | | u^2+-5u+4=0 | | 26.3d=12 | | 17-7x=-8(-7+6x)+2x | | u2+-5u-4=0 | | 9/5a=4/3 | | 2x+1+x-3=4x-9 | | 15y-30=150+50y | | .357/1.009=3.4/z | | 11−a=−23 | | x+(12/100)x=19.04 | | 5n=12/4 | | 11-3p=2/3p | | x(x+4)=960 | | 48=8(1x+1) | | -2.16=-0.4(n-2.1) |

Equations solver categories